(untitled) (Architecture Image Studies, 2026)
Sustainable Human Resource Management (Sustainable HRM) has emerged as a strategic approach that integrates economic, social, and environmental objectives into organizational HR practices. However, empirical evidence explaining how internal HR mechanisms contribute to Sustainable HRM, particularly within training institutions and cross-sector companies, remains limited. This study aims to examine the influence of a Kaizen-based HR reward system on Sustainable HRM through multiple mediation mechanisms involving employee commitment, employee culture, situational leadership, and employee performance, while also testing the moderating role of employee experience. Using a quantitative explanatory design, data were collected from managerial-level employees across companies in West Java that collaborate with vocational training institutions (LPK “X”). Structural Equation Modeling (SEM) was employed to analyze direct, indirect, and moderating effects within the proposed integrative framework. The findings indicate that the reward system significantly influences employee commitment, employee culture, and situational leadership. Employee performance plays a crucial mediating role in strengthening Sustainable HRM implementation. Furthermore, employee experience moderates several relationships within the model, particularly in strengthening the linkage between behavioral factors and performance outcomes. This study contributes theoretically by extending Sustainable HRM literature through the integration of Goal Setting Theory and Kaizen-based HR practices into a comprehensive structural model. Practically, the results provide strategic guidance for organizations in designing adaptive reward systems and fostering sustainable employee development. The findings also offer policy implications for training institutions seeking to enhance long-term workforce sustainability.